Comparison of registry and government evaluation data to ascertain severe trauma cases in Japan. Issue 4 (7th August 2017) - Nakahara, Shinji; Sakamoto, Tetsuya; Fujita, Takashi; Koyama, Tomohide; Katayama, Yoichi; Tanabe, Seizan; Yamamoto, Yasuhiro
Abstract : Aims: Accurate evaluation of health care quality requires high‐quality data, and case ascertainment (confirming eligible cases and deaths) is a foundation for accurate data collection. This study examined the accuracy of case ascertainment from two Japanese data sources. Methods: Using hospital‐level data, we investigated the concordance in ascertaining trauma cases between a nationwide trauma registry (the Japan Trauma Data Bank) and annual government evaluations of tertiary hospitals between April 2012 and March 2013. We compared the median values for trauma case volumes, numbers of deaths, and case fatality rates from both data sources, and also evaluated the variability in discrepancies for the intrahospital differences of these outcomes. Results: The analyses included 136 hospitals. In the registry and annual evaluation data, the median case volumes were 120.5 cases and 180.5 cases, respectively; the median numbers of deaths were 11 and 12, respectively; and the median case fatality rates were 8.1% and 6.4%, respectively. There was broad variability in the intrahospital differences in these outcomes. Conclusions: The observed discordance between the two data sources implies that these data sources may have inaccuracies in case ascertainment. Measures are needed to evaluate and improve the accuracy of data from these sources. Abstract : We compared case ascertainment in the Japan Trauma Data Bank and the annual government evaluation of tertiary hospitals. There was considerable discordance between the two data sources. Measures are needed to improve data quality in these data sources